The Tenure of Land by Foreigners through Nominee Agreements & Waarmerking by Notaries - Anisa Amalia; Umar Ma'ruf (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Land tenure between foreigners and Indonesian citizens through a nominee agreement is an effort made so that foreigners own land in Indonesia with Own rights status, which is done by borrowing the name of the Indonesian citizen to be included in the land certificate. However, this is contrary to the applicable laws and regulations. The problem in this research is what are the legal consequences of land tenure by foreigners through a nominee agreement made under the hand and waarmerking by a notary in Jepara Regency. This study uses an empirical juridical approach. The research specification is descriptive analytical, the type of data comes from primary data obtained through field studies and secondary data through library studies. Methods of collecting data through interview techniques, literature studies and document studies. The method of data analysis is descriptive qualitative. The results of the study indicate that the practice of land tenure through nominee agreements made under the hands of foreigners and Indonesian citizens with the aim that foreigners can control land with property rights status like Indonesian citizens is legally a form of legal smuggling so that the agreement is not valid or deemed to have never existed and resulting in the sale and purchase of the land being null and void and the land falling to the state, this is based on Article26 paragraph (2) BAL.